2015
DOI: 10.7861/clinmedicine.14-6-74
|View full text |Cite
|
Sign up to set email alerts
|

Diseases from North America: focus on tick-borne infections

Abstract: Tick-borne infections are seen throughout the United States, with varying geographical locations. Many of these infections are also increasingly seen in Europe. Certain ticks (eg Ixodes) can transmit more than one infection. Diagnosis, particularly in early infection, can be challenging and therefore knowledge of the distinguishing clinical features and epidemiology of these diseases is important. Testing for Lyme disease often causes confusion for patients and medical providers, as serological tests may be ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Thus, in such patients with suggestive exposure history, closer follow up and perhaps a lower threshold for workup is advised. It has been suggested that doses of antibiotics be augmented in the immunocompromised as well [249].…”
Section: Travel Medicine: When To Consider Tick-borne Diseasesmentioning
confidence: 99%
“…Thus, in such patients with suggestive exposure history, closer follow up and perhaps a lower threshold for workup is advised. It has been suggested that doses of antibiotics be augmented in the immunocompromised as well [249].…”
Section: Travel Medicine: When To Consider Tick-borne Diseasesmentioning
confidence: 99%
“…It is also suggested that chronic B. microti parasite-positive but asymptomatic infection lasting more than 3 months are also treated with this same combination [95]. However, in immunocompromised individuals or any severe case with symptoms of severe hemolysis, renal or hepatic distress, compromised respiratory function, or a parasitemia greater than 10%, regardless of species, a 10 day course of intravenous clindamycin plus quinine coupled with exchange transfusion is the recommended course of treatment [41, 44, 96]. The additive measure of exchange transfusion swiftly removes the parasitized RBCs from the host circulation, resolving any pathologies arising from anemia, such as low hematocrit and circulating toxic metabolites which released into the host’s circulatory system from the cyclical destruction of the RBCs.…”
Section: Diagnosis and Treatment Of Babesiosismentioning
confidence: 99%
“…For instance, in the case of Lyme disease, the tick-borne bacterium Borrelia burgdorferi possesses mechanisms to evade the host’s immune system by altering its surface proteins, antigenic variation, and immune modulatory factors. This allows the bacterium to establish persistent infection and cause the characteristic symptoms of Lyme disease ( Brites-Neto et al., 2015 ; Nathavitharana and Mitty, 2015 ; Sparagano et al., 2022 ). Interestingly, ticks have developed remarkable strategies to coexist with these diverse disease-causing pathogen challenges.…”
Section: Introductionmentioning
confidence: 99%